Reallocated Sectors Count Parameter for Analysing Hdd Reliability - Nailovich Nasyrov, Iskandar; Iskandarovich Nasyrov, Ildar; Iskandarovich Nasyrov, Rustam; Askarovich Khairullin, Bulat (International Journal of Psychosocial Rehabilitation, 2019)
The dependence of the SMART parameter 5 Reallocated sectors count value change on the operating time characterising the number of reallocated sectors is considered. This parameter is critical in the sense that if the attribute value increases, this may indicate deterioration in the state of the disk surface. The scientific task of the study is to establish relationships in the failed hard drives between the specified parameter and the values of other reliability parameters for information stores of various manufacturers. In the course of the study, the drives of the HGST, Hitachi, Samsung, ST, Toshiba, WDC trademarks operated in the Backblaze largest commercial data centre were analysed. The analysis revealed a relationship between the specified parameter and the parameters 1 Read error rate (frequency of errors (when reading data from the disk), the origin of which is due to the hardware of the disk), 196 Reallocation event count (number of reallocation operations), 197 Current pending sector count (number of sectors that are candidates for reallocation). It is shown that the nature of the change in the values of the considered parameters depends on the manufacturer of information storage devices. It is proposed to perform an individual assessment of the reliability of hard drives using the parameters identified as a result of the study.